2017
DOI: 10.1590/2358-2936e2017013
|View full text |Cite
|
Sign up to set email alerts
|

Designation of a new genus Michaelimenes (Decapoda: Caridea: Palaemonidae), with new host record and range extension of its type species, M. perlucidus (Bruce, 1969)

Abstract: Designation of a new genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Remarks: The stepwise revision of the problematic genus Periclimenes (e.g., [8,22,38]) resulted in the description of new genera and revalidation of several previously synonymised genera over the last two decades (e.g., [10,20,36,[39][40][41][42][43][44]). The molecular analysis of selected, mainly symbiotic palaemonid taxa by Horká et al [8] showed multiple host switches and adaptive convergences, which impeded the genus-level taxonomy within this group.…”
Section: Palaemonidae Rafinesque 1815mentioning
confidence: 99%
“…Remarks: The stepwise revision of the problematic genus Periclimenes (e.g., [8,22,38]) resulted in the description of new genera and revalidation of several previously synonymised genera over the last two decades (e.g., [10,20,36,[39][40][41][42][43][44]). The molecular analysis of selected, mainly symbiotic palaemonid taxa by Horká et al [8] showed multiple host switches and adaptive convergences, which impeded the genus-level taxonomy within this group.…”
Section: Palaemonidae Rafinesque 1815mentioning
confidence: 99%
“…The caridean shrimp genus Periclimenes Costa, 1844 [1], is currently represented by eight species in the eastern Atlantic Ocean and Mediterranean Sea: P. aegylios Grippa and d'Udekem d'Acoz, 1996 [2]; P. amethysteus (Risso, 1827) [3]; P. andresi MacPherson, 1988 [4]; P. eleftherioui Koukouras and Turkay, 1996 [5]; P. granulatus Holthuis, 1950 [6]; P. kornii (Lo Bianco, 1903) [7]; P. sagittifer (Norman, 1861) [8]; and P. scriptus (Risso, 1822) [9,10]. Periclimenes wirtzi d'Udekem d'Acoz, 1996 [10] was recently transferred to the genus Michaelimenes Okuno, 2017 [11], by Anker et al (2023) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The deep-sea palaemonid shrimp fauna of the Indo-West Pacific is relatively well documented, with to date 23 genera and about 84 species recorded from depths of more than 100 m by trawling and dredging ( Bruce, 1991 ; De Grave & Fransen, 2011 ; Kou, Li & Bruce, 2016 ; Li, Mitsuhashi & Chan, 2008 ; Marin & Chan, 2014 ; Mitsuhashi & Chan, 2006 ; Okuno, 2017 ; Wang, Chan & Sha, 2015 ). Among them is the rarely recorded genus, Mesopontonia Bruce, 1967 which can be distinguished from related genera by the combination of the absence of both supraorbital and antennal teeth on the carapace, as well as the absence of an exopod on the third maxilliped ( Bruce, 1967 ; Bruce, 1995 ; Chace & Bruce, 1993 ).…”
Section: Introductionmentioning
confidence: 99%